A waste-free, microbial oil centered cyclic bio-refinery approach based on flexible macroalgae biomass. (15th August 2018) - Masri, Mahmoud A.; Jurkowski, Wojciech; Shaigani, Pariya; Haack, Martina; Mehlmer, Norbert; Brück, Thomas
Graphical abstract: Highlights: Holistic valorization of unexploited marine biomass. Integrated production of plant like yeast lipids, animal feed and biosorbents. Enzymatic macroalgae liquefaction to obtain yeast cultivation media. Utilization of hydrolysis residues as precious metal biosorbent. New, simple and rapid analysis tools for industrial lipid/ biosorption monitoring. Abstract: Biofuels and the oleochemical industry are highly dependent on plant oils for the generation of renewable product lines. Consequently, production of plant lipids, such as palm and rapeseed oil, for industrial applications competes with agricultural activity and is associated with a negative environmental impact. Additionally, established chemical routes for upgrading bio-lipids to renewable products depend on metal-containing catalysts. Metal leaching during oil processing results in heavy metal contaminated process wastewater. This water is difficult to remediate and leads to the loss of precious metals. Therefore, the biofuels and chemical industry requires sustainable solutions for production and upgrading of bio-lipids. With regard to the former, a promising approach is the fermentative conversion of abundant, low-value biomass into microbial, particularly yeast-based lipids. This study describes the holistic, value-adding conversion of underexploited, macroalgae feedstocks into yeast oil, animal feed and biosorbents for metal-based detoxification of process wastewater. The initial step comprises a selective enzymatic liquefaction step that yields a supernatant containing 62.5% and 59.3% ( w / d w biomass ) fermentable sugars from L. digitata and U. lactuca, respectively. By dispensing with chemical pretreatment constraints, we achieved a 95% ( w / w ) glucose recovery. Therefore, the supernatant was qualified as a cultivation media without any detoxification step or nutrition addition. Additionally, the hydrolysis step provided 27–33% ( w / d w biomass ) of a solid residue, which was qualified as a metal biosorbent. Cultivation of the oleaginous yeast C. oleaginosus on the unprocessed hydrolysis supernatant provided 44.8 g L −1 yeast biomass containing 37.1% ( w / d w biomass ) lipids. The remaining yeast biomass after lipid extraction is targeted as a performance animal feed additive. Selectivity and capacity of solid macroalgae residues as biosorbents were assessed for removal and recycling of rare and heavy metals, such as Ce +3, Pb +2, Cu +2 and Ni +2 from model wastewater. The biosorption capacity of the macroalgae residues (sorption capacity ∼ 0.7 mmol g −1 ) exceeds that of relevant commercially available adsorption resins and biosorbents. To facilitate the integration of our technology in existing chemical and biotechnological production environments, we have devised simple, rapid and cost-efficient methods for monitoring both lipogenesis and metal sorption processes. The application of the new optical monitoring tools is essential to determine yeast cell harvesting times and biosorption capacities respectively. For the first time we report on a waste-free bioprocess that combines sustainable, microbial lipid production from low value marine biomass with in-process precious metal recycling options. Our data allowed for a preliminary economic analysis, which indicated that each product could be cost competitive with current market equivalents. Hence, the synaptic nature of the technology platform provides for the economic and ecologic viability of the overall process chain.